Digitized : industry transformation and disruption through entrepreneurship and innovation - Einav, Gali (United Kingdom : Emerald Publishing, 2019)
Over the past ten years, industries such as music, retail, journalism, advertising, and health information have experienced massive and wrenching disruption. Dominant players have been displaced and often marginalized by innovative, entrepreneurial competitors. The same digital transformation has now migrated to more traditional sectors. Just as the Industrial Revolution created distinct winners and losers, so the digital era has led to a climate where individuals, companies, and even entire industries and countries will either thrive or fall hopelessly behind. Gali Einav and a strong group of international contributors offer a guide to this brave new world in a timely collection that combines academic insights and entrepreneurial case studies focused on digital innovation. A first section brings together academic thought-leaders to offer in-depth perspectives on changes in the digital domain, and focusing these insights around real-world examples, a second section showcases insights into four technology startups that have disrupted their industries through digital innovation. By exploring the effect of disruptive technologies within media, health, music, and employment, this book helps readers to take their next steps into the digital future. For its combination of academic rigor and practical, real-world case studies, Digitized is essential reading both for researchers of innovation and entrepreneurship and for innovators and entrepreneurs across industries.
Media innovation meets the marketplace / John Carey -- From interactive television to digital health : insights for industries in transformation / Gali Einav and Hal Wolf -- How music technology will impact personal creative expression / Daniel V. Oppenheim, Andrew Phillips and Revital Hollander -- Back to the future : user research as a critical tool for novel design / Shuli Gilutz -- The psychology of customer experience / Liraz Margalit -- The perspective / Daniel Ravner -- Perpetix / Nathan Lipson -- Data : a love story / Tania Yuki -- The argument for the inclusion of self-reported sentiment and skill data in visual professional coaching / Lydia Loizides.
Includes bibliographical references and index.
Keywords: Information technology -- Economic aspects; Internet -- Economic aspects; Knowledge economy; New business enterprises -- Technological innovations; Commerce -- Technological innovations; Entrepreneurship; Technological innovations; Digital media -- Economic aspects; Digital media -- Social aspects